TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 2019 DOMAIN ALIGN PLAN AND ORGANIZE STUDI KASUS: AKADEMI KOMUNITAS DARUSSALAM BLOKAGUNG BANYUWANGI - Aziz, Moh Abdul; Kusrini, Kusrini; Nasiri, Asro (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
The role of information technology (IT)continues to experience a very significant increase in building and facilitating the performance of a company or institution. The use of IT in educational institutions is theoretically believed to be able to provide convenience and efficiency in administration. Akademi Komunitas Darussalam (AKD) Blokagung Banyuwangi is a relatively new higher education institution, with the 2019 Establishment Decree proving that the institution is not yet five years old. Like a new institution, many unresolved issues must be addressed, one of which is in the field of IT governance in optimizing the performance of human resources in the field of information technology. Therefore, it is necessary to design information technology governance related to the management of IT human resources. This research will design governance using the COBIT 2019 framework. The focus of this research is the Align, Plan, and Organize (APO) domain in the APO07 Manage Human Resources sub-domain. The results of the gap analysis carried out resulted in design recommendations on the people aspect in the form of adjustments to organizational structure, details of main tasks and functions, planning training and workshops, as well as communication in the form of meetings. In the process aspect, it produces SOPs, reporting schemes, and alignment of problem-solving. On the technology aspect, in the form of recommendations for human resource information system tools. This research is expected to assist the AKD Blokagung in carrying out recommendations based on the roadmap that has been adjusted to the AKD Blokagung long-term plan so that it can prioritize IT human resource management in the IT sector according to the needs of the AKD Blokagung. Keywords: Information Technology, COBIT 2019, IT Governance, APO07.